Development of Interactice Powerpoint on the Subject of Aqeeda Akhlak for Grade IX - Dina Farikhah; Safrina Ariani; Masbur Masbur (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2024)
The lack of varied learning media results in students' interest and desire to learn being weak or lacking, especially in PAI teaching media. So, one solution is to provide interactive learning media for students. The purpose of this study was to develop PowerPoint learning media products on Aqeeda Akhlak material at MTsN 3 Aceh Besar and to determine the level of practicality and teacher and student responses to the products produced. This study uses a research and development method with the 4D development model (Define, Design, Development, and Dissemination) developed by Thiagarajan. Data collection techniques were carried out using validation sheets, and teacher and student response questionnaires. The products researchers produced are 2 PowerPoint media on Faith in the Last Day for the odd semester and Avoiding Deviant Behavior in Teenage Associations for the even semester. The percentage of final validation results in the material field is 85%, and the rate of results in the media field is 95.5%. The total percentage of validators was 90.25% with the category â€œVery Validâ€. Teacher response was 95% with the category â€œStrongly Agreeâ€, while student response was 93.35% with â€œStrongly Agreeâ€. The results showed that the PowerPoint learning media developed was feasible to use as Aqeeda Akhlak learning media